114 Leading a quality improvement project across a London-based sexual health service. (3rd November 2019) - Alam, Vardah; Yin, Lucia; Khan, Hadiya; Tincknell, Laura; Wallis, Emma; Sethi, Gulshan
Abstract : Background: Recent BASHH Guidelines recommend testing for Mycoplasma genitalium (MG) in clinically indicated conditions (CIC); non-gonococcal urethritis (NGU); epididymo-orchitis; pelvic inflammatory disease (PID). The aim of this quality improvement project was to ensure that 100% of clinically indicated patients were tested for MG across the Guy's and St Thomas' trust Sexual Health service. Method: Baseline data was collected over five weeks and it was identified that the median number of clinically indicated MG tests carried out were as follows: 60% for NGU, 63% for PID and 100% for epididymo-orchitis. Subsequently, three Plan-Do-Study-Act (PDSA) cycles were planned: Ensuring that all staff had IT access to the order set for MG by liaising with the relevant staff Holding a departmental educational event about testing for MG in conjunction with displaying posters clinical areas Sending reminder emails to clinicians who didn't test clinically indicated patients for MG. A sample of 10 patients for each CIC per week were analysed to identify the percentage tested for MG; results were plotted on run charts. Results: There was a sustained increase in the number of NGU cases appropriately tested for MG following the cycles. No increase in MG testing was seen in PID and epididymo-orchitis, however, the median number of patients each week was low (7.8 and 2.3 respectively). The rate of inappropriate testing for MG was also analysed and found to be high at 15%. Discussion: We have demonstrated sustained improvement in MG testing in NGU patients but not for the other CICs; the significant number of inappropriate tests performed warrants further work. Key staff members were involved in the planning stages of the project and therefore, were made aware of the changes through meetings, emails and the teaching event held. This optimised staff involvement and meant that we were able to gain feedback.